Hubungan Dukungan Sosial dengan Derajat Depresi Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis di RSUD Dr.Moewardi - Dwi Adhi Nugraha; Istar Yuliadi; Rifai Hartanto (Nexus Kedokteran Klinik, 2012)
Background: Chronic kidney disease incidences are expected to rise. One of the most pshycopatological problems in hemodyalisis patient is depression. Depression will decrease compliance, immnune dysfunction, and poor nutrition. This study aimed to know prevalence of depression and to search wether there were some relationship between social support with depression in hemodyalisis at RSUD Dr.Moewardi. Methods: This was an analitic observational study. Two measurement tools were used in this study, they were Beck Depression Inventor (BDI) and modified Multidimensional Support of Perceived Social Support (MSPSS). 30 patients were involved in this study. Statistic tests used in this study were Pearson test and Spearman test. Results: Depression was found in 43.33% chronic kidney disease patient undergoing hemodyalisis, with BDI cutoff >15. Mean of BDI score was 16.3 and deviation standard score was 7.433. Depression has significant negative relationship with family support, r = -0.480 and p = 0.007 (< 0.05). No significant relationship between social support from other source outside family with degree of depression. Conclusions: Depression was found in hemodyalisis patients at RSUD Dr.Moewardi. Degree of depression could be decreased by family support. Keywords: Social support, depression, chronic kidney disease, hemodyalisis